A primer on proning in the emergency department. Issue 6 (4th July 2020) - McGurk, Kevin; Riveros, Toni; Johnson, Nicholas; Dyer, Sean
Abstract: Historically, the prone position was used almost exclusively in the ICU for patients suffering from refractory hypoxemia due to acute respiratory distress syndrome (ARDS). Amidst the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) pandemic, however, this technique has been increasingly utilized in settings outside of the ICU, particularly in the emergency department. With emerging evidence that patients diagnosed with COVID‐19 who are not intubated and mechanically ventilated may benefit from the prone position, this strategy should not be isolated to only those with critical illness. This is a review of the pertinent physiology and evidence supporting prone positioning along with a step‐by‐step guide meant to familiarize those who are not already comfortable with the maneuver. Placing a patient in the prone position helps to improve ventilation‐perfusion matching, dorsal lung recruitment, and ultimately gas exchange. Evidence also suggests there is improved oxygenation in both mechanically ventilated patients and those who are awake and spontaneously breathing, further reinforcing the utility of the prone position in non‐ICU settings. Given present concerns about resource limitations because of the pandemic, prone positioning has especially demonstrable value as a technique to delay or even prevent intubation. Patients who are able to self‐prone should be directed into the ''swimmer's position'' and then placed in reverse Trendelenburg position if further oxygenation is needed. If a mechanically ventilated patient is to be placed in the prone position, specific precautions should be taken to ensure the patient's safety and to prevent any unwanted sequelae of prone positioning.